IS26-Mediated Genetic Rearrangements in Salmonella Genomic Island 1 of Proteus mirabilis - Wang, Xue-Chun; Lei, Chang-Wei; Kang, Zhuang-Zhuang; Zhang, Yu; Wang, Hong-Ning (Frontiers in Microbiology, 2019)
Salmonella genomic island 1 (SGI1) is an integrative mobilizable element integrated into the chromosome of bacteria, which plays an important role in the dissemination of antimicrobial resistance genes. Lots of SGI1 variants are found mainly in Salmonella enterica and Proteus mirabilis. In this study, a total of 157 S. enterica and 132 P. mirabilis strains were collected from food-producing animals in Sichuan Province of China between December 2016 and November 2017. Detection of the SGI1 integrase gene showed that three S. enterica and five P. mirabilis strains were positive for SGI1, which displayed different multidrug resistance profiles. Five different SGI1 variants, including two novel variants (SGI1-PmBC1123 and SGI1-PmSC1111), were characterized by whole genome sequencing and PCR linkage. In two novel SGI1 variants, IS26-mediated rearrangements resulted in large sequence inversions of the MDR regions extending outside the SGI1 backbone. The sul3-type III class 1 integron (5′CS-sat-psp-aadA2-cmlA1-aadA1-qacH-IS440-sul3) and gene cassettes aac(6′)-Ib-cr-blaOXA–1-catB3-arr-3 are found in SGI1-PmSC1111. Mobilization experiments indicated that three known variants were conjugally mobilized in trans to Escherichia coli with the help of a conjugative IncC plasmid. However, the two novel variants seemed to lose the mobilization, which might result from the sequence inversion of partial SGI1 backbone. The identification of the two novel SGI1 variants in this study suggested that IS26-mediated rearrangements promote the diversity of SGI1.